Auto-level System on 3D Printer Bed Using Arduino and 3D Touch Probe Sensor - Alexander Ariantono (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The development of technology today has emerged the latest technology in three-dimensional (3D) printer machines. Problems faced by 3D printers include the position of the printer bed that is not horizontal. The position of the printer bed that is not horizontal will cause the 3D print to be skewed. To overcome the problem of tilting the bed of a 3D printer, the auto-level system is needed, which is a system that can correct the position of the base so that it becomes horizontal. In this study, an auto-leveling system was designed and made for four 3D printing base support positions. The drive for the printing press uses a stepper motor with a worm gear transmission. The controller uses an Arduino board and tested various position sensors to determine the slope of the base. The sensor tested is a 3D touch probe sensor. From the test results, the 3D touch probe sensor has a height value difference of not more than 0.05mm from each measurement position. The print base slope reference point is at the center point of the print base. The position of the other corner of the base will be adjusted in height with a stepper motor drive